2018
DOI: 10.1097/pts.0000000000000542
|View full text |Cite
|
Sign up to set email alerts
|

Risk Management in the Ambulatory Care Process in a Mutual Benefit Association Covering Work-Related Accidents and Diseases: Applying Modified Failure Mode and Effect Analysis (FMEA) Methodology

Abstract: To assess the impact of different forms of use of failure mode and effect analysis methodology for risk prioritization in the ambulatory care process in a mutual benefit association covering work-related accidents and diseases. Methods:The study is based on a previously drafted and individually prioritized risk map by a multidisciplinary team made up of patient safety committee members from health care centers and clinics in a mutual benefit association covering work-related accidents and diseases. The profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
(39 reference statements)
0
3
0
1
Order By: Relevance
“…The importance of multidisciplinary collaboration has been reported in resuscitation in life crises 40 – 42) and in rehabilitation 43 47) . The results suggest the need for RPs to acquire the ability to respond to unexpected events, and to practice responding promptly and appropriately together with other professionals.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of multidisciplinary collaboration has been reported in resuscitation in life crises 40 – 42) and in rehabilitation 43 47) . The results suggest the need for RPs to acquire the ability to respond to unexpected events, and to practice responding promptly and appropriately together with other professionals.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the ability of tools to predict suicide is low. Other studies conducted in general hospitals using FMEA identified failures in medication reconciliation or in other treatments provided, 9,10,15,24,25 adjusting correct medication dosage in critical events and communication difficulties between medical staff, relatives, and patients during a hospitalization or treatment. 26 These problems increased during the COVID-19 period.…”
Section: Discussionmentioning
confidence: 99%
“…FMEA has been used by the engineering community since the 50s and was adopted in the development of HFMEA (DeRosier et al, 2002). Since it has been around for a longer time, several papers in healthcare settings still follow FMEA steps or modify FMEA by themselves to better adjust their needs (Alimohammadzadeh et al, 2017;Ghoushchi et al, 2021;Grau et al, 2021;Hakiem et al, 2022;Paradis et al, 2021). Patient safety, risk management, and risk assessment were among the top five most used author keywords.…”
Section: Discussionmentioning
confidence: 99%